Business angels: Crucial elements of the European financial ecosystem - Maikel Pellens; Georg Licht (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2017)
Europe faces a conundrum. Despite high levels of research investment and leading the market in many industries, disruptive and radical innovation typically does not come from European startups. One of the reasons for this is financial constraints: most innovative European start-ups do not manage to attract institutional funders or venture capitalists to invest in their growth, and hence do not fulfill their growth potential. Business angels, individual investors who support early-stage firms with capital and experience, are believed to be able to fill this gap in the funding landscape and thus help boost European innovation. However, relatively little is known about business angel activities in Europe. In this policy brief, we summarize recent research conducted at the Centre for European Economic Research (ZEW), highlight trends in the German and European business angel markets, and discuss implications for the design of policies aimed at fostering the development of markets for business angel investment.
Keywords: 330